2022
DOI: 10.1155/2022/5401760
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect and Possible Mechanisms of Artemisinin and Its Derivatives for Diabetic Nephropathy: A Systematic Review and Meta-Analysis in Animal Models

Abstract: Background. Artemisinin and its derivatives have potential antidiabetic effects. There is no evaluation of reported studies in the literature on the treatment of diabetic nephropathy (DN), one of the commonest diabetic microangiopathies, with artemisinins. Here, we aimed to evaluate preclinical evidence for the efficacy and possible mechanisms of artemisinins in reducing diabetic renal injury. Methods. We conducted an electronic literature search in fourteen databases from their inception to November 2021. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Systematic review and meta-analysis showed that artemisinin has a protective effect on DN ( Feng et al, 2022 ). STZ-induced experimental DN model was treated with artemether combined with enalapril; the expression of catalase (CAT) was upregulated, SOD and urinary albumin excretion (UAE) were downregulated, and glomerular hypertrophy was relieved ( Chen et al, 2022 ).…”
Section: Role Of Artemisinin and Its Derivatives In Kidney Diseasementioning
confidence: 99%
“…Systematic review and meta-analysis showed that artemisinin has a protective effect on DN ( Feng et al, 2022 ). STZ-induced experimental DN model was treated with artemether combined with enalapril; the expression of catalase (CAT) was upregulated, SOD and urinary albumin excretion (UAE) were downregulated, and glomerular hypertrophy was relieved ( Chen et al, 2022 ).…”
Section: Role Of Artemisinin and Its Derivatives In Kidney Diseasementioning
confidence: 99%
“…Cell cytosol release of ALT and AST can be caused as secondary cell necrosis shifts [17]. High ALT and AST activities comprise a high fluidity of the hepatic micromembrane, free radical growth, and modification of the liver tissue [18].…”
Section: Ns: Non Significantmentioning
confidence: 99%
“…4 Furthermore, ART has demonstrated multiple beneficial effects in animal models of diabetic nephropathy. 5 However, whether ART could also be applied in the treatment of ORG has yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%